Escape Under the Forever Sky : A Novel - Yohalem, Eve (San Francisco : Chronicle Books, 2009)
As a future conservation zoologist whose mother is the United States Ambassador to Ethiopia, thirteen-year-old Lucy uses her knowledge for survival when she is kidnapped and subsequently escapes.
Keywords: Wilderness survival -- Fiction; Kidnapping -- Fiction; Mothers-daughter relationship -- Fiction; Ethiopia -- Fiction